2018
DOI: 10.1111/ocr.12251
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among tongue volume, hyoid position, airway volume and maxillofacial form in paediatric patients with Class‐I, Class‐II and Class‐III malocclusions

Abstract: Objectives:To clarify the associations among tongue volume, hyoid position, airway volume and maxillofacial form using cone beam computed tomography (CBCT) data for children with Class-I, Class-II and Class-III malocclusion. Setting and SamplePopulation: Sixty children (mean age, 9.2 years) divided into Class-I, Class-II and Class-III malocclusion groups according to the A-nasion-B angle. Material and Methods: Cone beam computed tomography was used for threedimensional reconstruction of the maxillofacial regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
0
16
0
5
Order By: Relevance
“…In previous studies, OCC and TV were measured using various techniques, such as MRI [20], CT [21,22], CBCT [9][10][11], and alginate impression material [12][13][14] . However, the anatomical definitions of the tongue and the measurement areas in these studies were usually inconsistent [20].…”
Section: Volumetric Analyses Of Tongue and Oral Cavity Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, OCC and TV were measured using various techniques, such as MRI [20], CT [21,22], CBCT [9][10][11], and alginate impression material [12][13][14] . However, the anatomical definitions of the tongue and the measurement areas in these studies were usually inconsistent [20].…”
Section: Volumetric Analyses Of Tongue and Oral Cavity Capacitymentioning
confidence: 99%
“…To better understand the influence of the tongue on the stability of the occlusion after orthognathic surgery, it is important to measure the volume of the oral cavity and tongue to determine the volumetric balance between OCC and TV. The OCC and TV have been measured accurately by cone-beam computed tomography (CBCT) examinations [9][10][11]. However, CBCT examinations involve exposure to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The most constricted area of the oropharyngeal airway is usually located at the base of the tongue [ 2 ]. At the same time, a positive correlation has been reported among tongue volume, pharyngeal airway and Sella-Nasion-B point (SNB) angle, while a negative correlation has been reported between tongue volume and A point-Nasion-B point (ANB) angle [ 3 ]. Finally, Class III patients might have higher risk of being mouth breathers than Class I patients (32% and 23%, respectively) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have also shown that the oropharyngeal region is wider in Class III individuals than in Class II individuals. 12 Takemoto et al evaluated the pharyngeal airway dimensions of prepubertal individuals with Class III malocclusion using cephalometric measurements. They found that females with Class III malocclusion had a lower pharyngeal airway size, however, larger than females with Class I occlusion.…”
Section: Introductionmentioning
confidence: 99%